Enzyme-free ethanol sensor based on electrospun nickel nanoparticle-loaded carbon fiber paste electrode - Liu, Yang; Zhang, L.; Guo, Q.; Hou, H.; You, T. (Elsevier BV, 2010)
We have developed a novel nickel nanoparticle-loaded carbon fiber paste (NiCFP) electrode for enzymefree determination of ethanol. An electrospinning technique was used to prepare the NiCF composite with large amounts of spherical nanoparticles firmly embedded in carbon fibers (CF). In application to electroanalysis of ethanol, the NiCFP electrode exhibited high amperometric response and good operational stability. The calibration curve was linear up to 87.5mMwith a detection limit of 0.25mM, which is superior to that obtained with other transition metal based electrodes. For detection of ethanol present in liquor samples, the values obtained with the NiCFP electrode were in agreement with the ones declared on the label. The attractive analytical performance and simple preparation method make this novel material promising for the development of effective enzyme-free sensors.